Vertical Structure of a Snowfall Event Based on Observations From the Aircraft and Mountain Station in Beijing - Huang, Yu; Zhao, Delong; Du, Yuanmou; Chen, Yichen; Zhang, Lei; Li, Xia; Jing, Yingying (Frontiers in Environmental Science, 2021)
Aircraft platform, ground-based disdrometer, cloud radar, radiometer and automatic station were combined to study a snowfall case (16:30-21:00 observed by ground cloud radar) on Yangqing Mountains in Beijing. Comparing the variation of ice habit, number concentration at aircraft altitude (2.9-3.2km) and ground, we discussed the ice growth mechanisms in Beijing Mountains. Results indicated that the snowfall was steady but not strong with reflectivity less than 20dBZ, and cloud top altitude less than 4.5km. The number concentrations for both liquid and ice crystal at aircraft altitude and ground were very similar, both dominated by small particles at diameter of 0.1-1.2mm, and the proportion of mean number concentration at small diameter both in aircraft and on the ground was large peaking at 44 L-1mm-1 and 8826 L-1mm-1 respectively, and decreased rapidly as diameter increased. There was no mixed phase in clouds with little liquid water. Particles were relatively regular, which were transparent with dendritic and disk-hexagonal. The ice crystals and snowflakes were mainly grown by the deposition and aggregation, rarely by the riming process, and no secondary ice formation was observed.